2023
DOI: 10.1021/acs.est.2c05404
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Designing a High-Performance Ultrafiltration Membrane Using Machine Learning

Abstract: Ultrafiltration (UF) as one of the mainstream membrane-based technologies has been widely used in water and wastewater treatment. Increasing demand for clean and safe water requires the rational design of UF membranes with antifouling potential, while maintaining high water permeability and removal efficiency. This work employed a machine learning (ML) method to establish and understand the correlation of five membrane performance indices as well as three major performance-determining membrane properties with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Data-driven research has received wide attention in the scientific community and has great potential in improving the design of materials. This study serves as a proof-of-concept for applying a meta-analytical approach to synthesize pre-existing data to determine patterns and make predictions, thereby obtaining a better understanding of the property–aggregation relationships of nanomaterials, which will be required for the development of accurate predictive models to estimate nanomaterial aggregation. This meta-analysis focused on carbon nanomaterials, and future analysis can include more types of nanomaterials (e.g., metal nanoparticles and nanoplastics) to evaluate the generalizability of the findings in this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data-driven research has received wide attention in the scientific community and has great potential in improving the design of materials. This study serves as a proof-of-concept for applying a meta-analytical approach to synthesize pre-existing data to determine patterns and make predictions, thereby obtaining a better understanding of the property–aggregation relationships of nanomaterials, which will be required for the development of accurate predictive models to estimate nanomaterial aggregation. This meta-analysis focused on carbon nanomaterials, and future analysis can include more types of nanomaterials (e.g., metal nanoparticles and nanoplastics) to evaluate the generalizability of the findings in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Other than the aggregation behavior of nanomaterials, their electronic structure and chemical activity are also property-dependent, and leveraging a meta-analytic approach to discover and define such relationships is well-suited . Also, with more data being generated, future studies could utilize more advanced meta-analytic techniques, such as machine learning , to better understand the interplay of multiple properties on the aggregation of nanomaterials and to provide potential practical aid in the design of nanomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…After a ML model is trained to predict membrane properties in the supervised manner, the SHAP package can be used to quantitatively analyze the correlation between the properties and membrane features. 36 In the work of Yang et al 33 (Figure 3), the SHAP value was used to interpret the multitask gas permeability prediction by a random forest (RF) and deep neural network (DNN) ensemble model. The models were trained to predict the permeability of 6 different gases (He, H 2 , O 2 , N 2 , CO 2 , and CH 4 ) through polymeric membranes.…”
Section: Membranes Using Xaimentioning
confidence: 99%
“…The SHapley Additive exPlanations (SHAP) package is a unified framework built on the basis of Shapley value to interpret ML predictions. After a ML model is trained to predict membrane properties in the supervised manner, the SHAP package can be used to quantitatively analyze the correlation between the properties and membrane features . In the work of Yang et al (Figure ), the SHAP value was used to interpret the multitask gas permeability prediction by a random forest (RF) and deep neural network (DNN) ensemble model.…”
Section: Data-driven Understanding Of Membranes Using Xaimentioning
confidence: 99%
“…Sensitivity analysis revealed that simulated permeability was more sensitive to changes in pore diameter than pore density (Figure 7b,c). Further studies, perhaps involving machine learning (ML) [46], could help elucidate how fabrication conditions and other structural parameters (e.g., pore connectivity, macrovoids in the substructure, and separation layer thickness) contribute to the experimentally observed property profiles, bringing us one step closer to realizing inverted designer cycles in the making of SNIPS-based UF membranes.…”
Section: Perspectives On Single-component Isv Snips: the Inverted Des...mentioning
confidence: 99%